TESTIMONIUM DE AUDITU SEBAGAI DASAR PERTIMBANGAN HAKIM DALAM MEMUTUS TINDAK PIDANA PENCABULAN DAN PERSETUBUHAN ANAK: Testimony by Hearing as the Basis for Judicial Consideration in Deciding Cases of Child Molestation and Rape - Fitra Triyana; Maria Silvya E. Wangga (Faculty of Law, Universitas Trisakti, 2024)
Decision No. 254/Pid.Sus/2023/Pn.Mks, which examined and adjudicated a case of sexual assault and intercourse, was based solely on Testimonium de auditu. The issue is to what extent the available evidence supports Decision No. 254/Pid.Sus/2023/PN.Mks in declaring the defendant not proven legally and convincingly guilty according to the applicable legal standards. The research method used involves secondary data and is structured using normative descriptive research techniques. The discussion and conclusion are that Asdar Muhammad should be charged with sexual assault and intercourse based on written evidence, witness statements, and testimony from a minor victim, according to the analysis conducted (Case No. 254/Pid.Sus/2023/PN.Mks). The importance of witness testimony compared to what is seen, heard, or experienced determines the severity of a case, based on Constitutional Court Decision No. 65/PUU-VIII/2010. However, Asdar Muhammad should have been found guilty of committing sexual assault or intercourse, rather than being declared not guilty, as stated in Constitutional Court Decision No. 65/PUU-VII/2010.